An Evaluation of MIKiR Learning in English Subject - Ruzaini Ruzaini (STAIN Bengkalis, 2021)
This paper aims to evaluate English learning on the components of the context, input, process, and product. This research is an evaluation research. Data were collected by observation, interview, and documentation then analyzed descriptively. The conclusions in this paper: 1) the value of the context of the initial condition of the institution is sufficient, the value of the input of the sub-components of facilities and infrastructure, sufficient teaching staff and curriculum, the value of the process of the planning and implementation of English learning is lacking, and the value of the product component on student learning outcomes; and 2) the recommendation of this paper, the head of the institution needs to review or change the implementation of the institution's curriculum for reform for a better direction, provided there are many English textbooks, teachers must make lesson plans based on the syllabus of competency units.Artikel ini bertujuan untuk mengevaluasi pembelajaran bahasa Inggris pada komponen context, input, process, dan product. Penelitian ini merupakan penelitian evaluasi. Pengumpulan data dilakukan dengan observasi, wawancara, dan dokumentasi kemudian dianalisis secara deskriptif. Kesimpulan dalam artikel ini: 1) nilai context untuk kondisi lembaga sudah cukup, nilai input untuk sarana dan prasarana, tenaga pengajar dan kurikulum memadai, nilai process untuk pembelajaran perencanaan dan pelaksanaan pembelajaran bahasa Inggris kurang, dan nilai komponen product terhadap hasil belajar siswa sudah cukup, dan 2) atas rekomendasi artikel ini, pimpinan lembaga perlu mengkaji ulang atau merubah implementasi kurikulum lembaga untuk reformasi ke arah yang lebih baik, dengan syarat buku teks bahasa Inggris yang banyak, guru harus membuat RPP berdasarkan unit kompetensi silabus.